LRCH1 polymorphisms linked to delayed encephalopathy after acute carbon monoxide poisoning identified by GWAS analysis followed by Sequenom MassARRAY® validation - Jiapeng Gu; Jiao Zeng; Xi Wang; Xin Gu; Xiaoli Zhang; Ping Zhang; Fan Zhang; Yongkai Han; Yazhou Han; Hongxing Zhang; Wenqiang Li; Renjun Gu (BMC, 2019)
Abstract Background We explored the association of leucine-rich repeats and calponin homology domain containing 1 (LRCH1) gene polymorphisms with genetic susceptibility to delayed encephalopathy after acute carbon monoxide poisoning (DEACMP), which might provide a theoretical basis for the pathogenesis, diagnosis, and prognosis research of DEACMP. Methods Four single nucleotide polymorphisms, rs1539177 (G/A), rs17068697 (G/A), rs9534475 (A/C), and rs2236592 (T/C), of LRCH1, selected as candidate genes through genome-wide association analysis, were genotyped in 661 patients (DEACMP group: 235 cases; ACMP group: 426 cases) using Sequenom Massarray®. The association analysis of four SNPs and LRCH1 was performed under different genetic models. Results LRCH1 polymorphisms (rs1539177, rs17068697, rs9534475) under additive and dominant genetic models were significantly associated with an increased risk of DEACMP, but no significant association under allele and recessive models was found. The LRCH1 rs2236592 polymorphism was susceptible to DEACMP only under the dominant model (TT/TC + CC, OR = 1.616, 95% CI: 1.092-2.390, P = 0.015784). In addition, the A allele gene of rs9534475 polymorphism in LRCH1 might increase the risk for DEACMP (OR = 1.273, 95% CI: 1.013-1.601, P = 0.038445). Conclusions We found a significant association between the four LRCH1 polymorphisms and DEACMP. The allelic A of rs9534475 polymorphism in LRCH1 might be a risk factor for DEACMP.